Effect of Combination of KMnO4 Oxidation and UV-C Radiation on Postharvest Quality of Refrigerated Pears cv. ‘Ercolini’ - Ramiro Alonso-Salinas; José Ramón Acosta-Motos; Antonio J. Pérez-López; Luis Noguera-Artiaga; Estrella Núñez-Delicado; Francisco Burló; Santiago López-Miranda (Horticulturae, 2022)
This present study proposes an improvement for the postharvest preservation of the ‘Ercolini’ pear, a fruit that is little tested in the field, using a combination of ethylene elimination methods. The techniques used were potassium permanganate filters in devices with ultraviolet radiation and constant air flow to favour the contact of ethylene with the oxidising agents. The analysis carried out included weight, diameter, firmness, soluble solids content, total acidity, maturity index, ascorbic acid concentration, total phenolic compounds, antioxidant capacity via the ORAC method and a descriptive sensory analysis using experts. In addition, the ethylene removal method was tested at two storage temperatures: 1 °C, near optimal temperature, and 8 °C, the standard temperature for transport and storage of fruit on a commercial scale. The results showed a marked improvement in the maintenance of postharvest physicochemical quality using the proposed combination of methods. The sensory analysis confirmed what was observed in the laboratory, with higher organoleptic quality values observed in pears treated with the complete system under study consisting of filter and machine, highlighting the greater presence of flavours and odours related to green fruit. Ultimately, this innovation could be highly relevant for the food industry.